Tissue explant coculture model of the hypothalamic–pituitary–gonadal–liver axis of the fathead minnow (Pimephales promelas) as a predictive tool for endocrine disruption. (21st June 2016) - Johnston, Theresa K.; Perkins, Edward; Ferguson, Duncan C.; Cropek, Donald M.
Abstract: Endocrine‐disrupting compounds (EDCs) can impact the reproductive system by interfering with the hypothalamic–pituitary–gonadal (HPG) axis. Although in vitro testing methods have been developed to screen chemicals for endocrine disruption, extrapolation of in vitro responses to in vivo action shows inconsistent accuracy. The authors describe a tissue coculture of the fathead minnow ( Pimephales promelas ) HPG axis and liver (HPG‐L) as a tissue explant model that mimics in vivo results. Brain (hypothalamus), pituitary, gonad, and liver tissue explants from adult fish were examined for function both individually and in coculture to determine combinations and conditions that could replicate in vivo behavior. Only cocultures had the ability to respond to an EDC, trenbolone, similarly to in vivo studies, based on estradiol, testosterone, and vitellogenin production trends, where lower exposure doses suppressed hormone production but higher doses increased production, resulting in distinctive U ‐shaped curves. These data suggest that a coculture system with all components of the HPG‐L axis can be used as a link between in vitro and in vivo studies to predict endocrine system disruption in whole organisms. This tissue‐based HPG‐L system acts as a flexible deconstructed version of the in vivo system for better control and examination of the minute changes in system operation and response on EDC exposure with options to isolate, interrogate, and recombine desired components. Environ Toxicol Chem 2016;35:2530–2541. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US Government work and, as such, is in the public domain in the United States of America.